Revitalisasi Kepemimpinan Tallu Batu Lalikan Mengatasi Krisis Lingkungan Di Toraja - Bunga, Sepriadi; Tiranda, Petrus; Ayamiseba, Glory Cristi (KINAA: Jurnal Kepemimpinan Kristen dan Pemberdayaan Jemaat, 2025)
This study aims to find a concept for revitalizing tallu batu lalikan collaborative leadership to create harmony between tallu and lolona. Tallu batu lalikan are three influential institutions in society, consisting of government institutions, religious institutions, and customary institutions. The urgency of this study stems from the ongoing environmental crisis in Toraja, which has caused environmental damage and various losses to the community because of the erosion of local wisdom values. Therefore, this study aims to identify collaborative measures that can be taken by the tallu batu lalikan as public servants to overcome the environmental crisis currently occurring in Toraja. These collaborative measures are based on the theory of collaborative leadership, which emphasizes collaboration between leaders in overcoming problems that are being faced together. This study uses a qualitative research method through field research and literature study. The results of this study indicate that the form of collaboration between the government, traditional leaders, and religious leaders in overcoming the environmental crisis in Toraja is only at the conceptual stage. The collaboration of tallu batu lalikan is limited to aligning perceptions through discussions. Only the church is quite active in building collaboration with the government and traditional leaders. The other two institutions have not been active in building collaboration, so it is hoped that they can actively and effectively build collaboration among tallu batu lalikan so that the environmental crisis in Toraja can be resolved.